Analysis of the dynamic characteristics of the cage of high-speed angular contact bearings under preloaded load. (January 2022) - Zeng, Guang; Liu, Bingyang; Bian, Qiang; Zhao, Chunjiang; Wen, Zhenhua; Zhang, Xiangyun; Chen, Ming; Zhang, Jinfeng
First, the law of motion of the bearing cage, inner ring, and ball are theoretically analyzed. Combining the nonlinear contact and deformation relationship between the various elements of the bearing, an explicit dynamic model of the high-speed angular contact bearing is established. Second, the stability and motion characteristics of the cage are analyzed from four aspects: the three-dimensional center of mass motion track of the cage with time, the deviation ratio of the center of mass vortex velocity, the angular velocity, and the linear velocity. The dynamic characteristics of the cage during the start-up phase of unsteady operation have been emphatically studied. The research results show that during the start-up phase, the greater the preload, the later the circle of the center of mass motion track of the cage expands outward, and the better the stability. The higher the rotation speed, the earlier the vortex trajectory circle of the center of mass of the cage expands outward, and the motion stability first strengthens and then weakens. Finally, the simulated value of the linear velocity of each bearing element changes with time are compared with the theoretical value, the correctness of the established explicit dynamic model was verified.